2011
DOI: 10.1089/neu.2009.1177
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cellular Transplantation Therapies for Spinal Cord Injury

Abstract: Cell transplantation therapies have become a major focus in pre-clinical research as a promising strategy for the treatment of spinal cord injury (SCI). In this article, we systematically review the available pre-clinical literature on the most commonly used cell types in order to assess the body of evidence that may support their translation to human SCI patients. These cell types include Schwann cells, olfactory ensheathing glial cells, embryonic and adult neural stem=progenitor cells, fate-restricted neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
465
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 496 publications
(474 citation statements)
references
References 173 publications
4
465
2
3
Order By: Relevance
“…To identify the cellular and molecular properties of NSPCs transplanted into chronically injured spinal cords, we combined flow-cytometric isolation and RNA-Seq. We found that NSPCs transplanted into chronically injured spinal cords have a sufficient capacity to produce therapeutic molecules and differentiate into neurons/oligodendrocytes [14]. However, chronic transplantation of NSPCs did not improve locomotor function after SCI.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…To identify the cellular and molecular properties of NSPCs transplanted into chronically injured spinal cords, we combined flow-cytometric isolation and RNA-Seq. We found that NSPCs transplanted into chronically injured spinal cords have a sufficient capacity to produce therapeutic molecules and differentiate into neurons/oligodendrocytes [14]. However, chronic transplantation of NSPCs did not improve locomotor function after SCI.…”
Section: Introductionmentioning
confidence: 81%
“…The success of stem cell-based strategies is strongly influenced by the timing of transplantation following SCI [14,15], which may be attributable to the changing environment of the injured spinal cord and the adaptation capacity of engrafted cells. Many researchers focused on elucidating pathophysiological processes during the acute and subacute phases of SCI [11,14], but the microenvironment of chronic SCI (more than 42 days after SCI) is still poorly understood.…”
Section: Cellular and Molecular Dynamics Of Traumatic Injured Spinal mentioning
confidence: 99%
See 3 more Smart Citations